2020
DOI: 10.1016/j.healun.2020.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial transplantation of atrial appendage micrograft patch salvages myocardium after infarction

Abstract: BACKGROUND: Ischemic heart disease remains the leading cause of mortality and morbidity worldwide despite improved possibilities in medical care. Alongside interventional therapies, such as coronary artery bypass grafting, adjuvant tissue-engineered and cell-based treatments can provide regenerative improvement. Unfortunately, most of these advanced approaches require multiple lengthy and costly preparation stages without delivering significant clinical benefits. METHODS: We evaluated the effect of epicardiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…In vitro studies have shown that mechanically obtained micrografts are enriched with mesenchymal progenitor cells, growth factors, and extracellular matrix components [19,23]. The technology has been successfully applied in different clinical contexts: dentistry field [13], dermatology for androgenetic alopecia [9,24], traumatology for chondropathy [14], osteonecrosis [15], and cardiology field for cardiac ischemia [16]. Our present result demonstrated that micrografts helped a severe intractable wound to generate qualified granulation tissue.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In vitro studies have shown that mechanically obtained micrografts are enriched with mesenchymal progenitor cells, growth factors, and extracellular matrix components [19,23]. The technology has been successfully applied in different clinical contexts: dentistry field [13], dermatology for androgenetic alopecia [9,24], traumatology for chondropathy [14], osteonecrosis [15], and cardiology field for cardiac ischemia [16]. Our present result demonstrated that micrografts helped a severe intractable wound to generate qualified granulation tissue.…”
Section: Discussionmentioning
confidence: 59%
“…Looking back at its history, this particular micrografts technology started with hair-containing punched tissues [9], and since then, different tissues have been subjected: skin [10], dermis [11], fat [12], periosteum [13], cartilage [14], bone [15], and atrial appendage [16]. The grafts may contain by themselves resident cells, progenitor cells, as well as various tissue factors including cytokines and growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…The right atrial appendage (RAA) is often manipulated during cardiac surgery to assemble bypass circulation. Moreover, RAA has been evaluated as a safe source for cardiac tissue for both diagnostic and therapeutic applications [ 115 ]. During the IHD-EPITRAN, a small RAA tissue sample, the size of which will be guided by clinical characteristics, will be collected from the study participants in cohorts II and III to enable an organ-specific characterization of the RNA epitranscriptomes ( Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported AAMs transplantation to improve the myocardium structurally and functionally after ischemic damage in a mouse model. 11 The multidisciplinary AADC consortium has successfully provided the leverage to translate these findings into clinical application initially as a clinical case report and description of methodology 10 and now here into the clinical safety and feasibility evaluation in support to CABG surgery. These results have thus paved the way for a more extensive further assessment of AAMs transplantation in terms of efficacy and safety, again relying on the wide cross-disciplinary expertise of AADC consortium partners.…”
Section: Translational Outlookmentioning
confidence: 99%
“…7, 8, 9 To this end, we have demonstrated the preclinical efficacy and initial clinical feasibility 10 of autologous cardiac microtissue, atrial appendage micrografts (AAMs), and have shown that AAMs therapy activates cardiogenic and cardioprotective pathways. 11 Based on these encouraging results, we initiated a phase I open-label, non- randomized clinical study 12 to evaluate the safety and feasibility of AAMs transplantation in conjunction with CABG surgery. We utilized gadolinium-enhanced cardiac magnetic resonance (CMR) imaging before and six months after treatment to gain detailed insight into the AAMs ‘efficacy to induce myocardial repair.…”
Section: Introductionmentioning
confidence: 99%